Polycystic ovary syndrome and the Rotterdam consensus work shop - Aparcana, Raúl (2015)
A review of polycystic ovarian syndrome (PCOS), a body comprising various symptoms and signs, among them mainly ovulation disorders, presence of hyperandrogenism and polycystic ovaries ago. It stresses the difference between the finding of polycystic ovaries and PCOS. The knowledge and study of PCOS in women of reproductive age is important because disturbances of menstruation and fertility she usually presents cosmetic problems caused by hyperandrogenism and an increased risk of developing diabetes mellitus and coronary heart disease future. Some conclusions of the recent consensus panel ESHRE / ASRM in Rotterdam on PCOS is included in this review.